Pengaruh Kualitas Pelayanan dan Kepuasan Terhadap Minat Kunjungan di Puskesmas Sangkapura - Umami, Syaiful; Nurwijayanti; Widyowati, Agustin (Fakultas Ekonomi Universitas Kadiri, 2024)
Increasing the quality of service will impact satisfaction and attract Interest in visits to public health services. This study aims to analyze the effect of service quality and satisfaction on Interest visits to Sangkapura public health services. The research method uses a cross-sectional study design. This research was conducted at the Sangkapura Public Health Center outpatient polyclinic starting in June-October 2022. There were 250 samples in the study with inclusion criteria, new patients, general patients, and patients who were at the Sangkapura Health Center and received services—sampling with a purposive sampling technique. The data analysis methods used were univariate analysis, chi-square, and multiple logistic regression tests. The results of the chi-square test showed that service quality (p-value 0.039 <0.05) had a significant effect on interest visits to Sangkapura public health services, satisfaction (p-value 0.000 <0.05) had a significant effect on the intention to interest visits to Sangkapura public health services. The results of the logistic regression test, namely satisfaction with a p-value of 0.001 and OR/(Exp(B))=4.995, quality of health services with a p-value of 0.028 and OR/(Exp(B)) = 2,792. The conclusion is that service quality and satisfaction affect interest in visits to Sangkapura public health services. However, satisfied patients are more influential and 4,995 times more interest in repeat visits to the Sangkapura Health Center.